Innovative Approaches to Teaching English to Legal English Student via Tricider Analysis - Gundary, Puspa; Triana, Neni; Gusparia, Gusparia (Journal of English Language and Education, 2024)
The need for technology in English Students of University of Riau is getting more and more advanced and developed. It is used in many aspects of law education including English course. Likewise, with the science of education and technology more and more students want to learn and gain knowledge. To solve the problem, in the first semeseter of English students  the authors conducted a survey at three classes of of University of Riau. The survey revealed students' expectations of learning English by Innovative Approaches Technology Via Tricide at university, their desire to improve their learning, and their knowledge of tecgnology. The results of the survey became the basis for the study. According to the results of the survey, the article summarizes and formulates recommendations for improving English language innovative Approaches technology for law students.